Clinical, Ultrasonographic and Histopathological Findings of Gastrointestinal Disorders in Cats - da Silva, Cristiane Aguero; Cunha, Simone Carvalhos dos Santos; de Souza, Heloisa Justen Moreira; de Jesus, Amanda Chaves; Ferreira, Ana Maria Reis (Acta Scientiae Veterinariae, 2018)
Background: Gastrointestinal disorders are common in cats, and the differentiation between inflammatory and neoplastic disease is essential to determine therapy. Therefore, ultrasonographic evaluation is an important tool for intestinal diagnosis in cats. The aim of this study is to evaluate the clinical, ultrasonographic and histopathological characteristics of cats with intestinal diseases. Materials, Methods & Results: Forty cats with gastrointestinal clinical signs and abdominal ultrasound findings consistent with inflammatory bowel disease or gastrointestinal neoplasia were studied. Ultrasound evaluated all abdominal organs, with emphasis on the gastrointestinal tract, and parameters included the thickness of gastric and intestinal wall, the variations of its echogenicity, reduced intestinal lumen, mesenteric lymph nodes, involvement of other abdominal organs and presence of abdominal effusion. All cats were referred to exploratory laparotomy, in order to obtain biopsy samples. Mean age was 11.6 years and there were 23 females and 17 males. Clinical signs included weight loss (87.5%), vomiting (82.5%), hyporexia (75%), diarrhea (35%), constipation (10%), polyphagia (5%) and intestinal gases (5%). In abdominal ultrasound, the most common findings were increased thickness of the gastric and/or intestinal wall, decreased echogenicity of the intestinal wall, reduction of the intestinal lumen due to severe wall thickening or presence of obstructive mass, and lymphadenopathy. Histopathology revealed alimentary lymphoma (AL) in 19 cases, inflammatory bowel disease (IBD) in 10 cases, intestinal adenocarcinoma in 7 cases, mast cell tumor in 2 cases and intestinal hemangiosarcoma in 2 cases. Discussion: Weight loss and vomiting were the two main complaints of the owners. However, diarrhea, described by previous authors as one of the main clinical signs in cats with intestinal diseases, was present in only 35% of cats of this study. The intestinal segments that were presented more frequently with increased wall thickness were duodenum and jejunum, and the mean wall thickness was 0.51 cm. Cats diagnosed with AL had mean value of duodenum wall thickness/jejunum of 0.564 cm, while in patients with IBD the mean value was 0.462 cm. Whereas previous authors said that ultrasonographic findings in cats with lymphocytic lymphoma are usually indistinguishable from patients with inflammatory bowel disease and that the wall thickness in both cases may be normal or increased, the analysis presented in this study was considered representative since most cases of AL corresponded to lymphocytic lymphoma. Surgery was performed on 35 cats in the study. The choice for exploratory laparotomy (instead of endoscopy for example) was to collect all layers of the intestinal segment, and it was successful, as all samples were representative and allowed the definitive diagnosis. Histopathology revealed 19 cases of alimentary lymphoma, 10 cases of inflammatory bowel disease, 7 cases of intestinal adenocarcinoma, 2 cases of intestinal mast cell tumor and 2 cases of intestinal hemangiosarcoma. The prevalence of AL over IBD has been previously discussed, but the occurrence of adenocarcinoma and mast cell tumor was higher in the present study. On feline physical examination, attention should be directed to abdominal palpation, since this study showed that 47.5% of the animals had intestinal wall thickening. The ultrasonographic evaluation and histopathological diagnosis is essential for the clinical management of cats with intestinal diseases.